Viral Environmental Warfare: Technology Bill of Rights Critically Needed - Herndon, J. Marvin; Whiteside, Mark (Advances in Social Sciences Research Journal, 2021)
The ongoing “hidden in plain sight” geoengineering operations including the pervasive, near global spraying of ultrafine particles into the troposphere pose an existential risk to the biosphere and humanity. Likewise, bioengineering and genetic manipulation of potential pandemic pathogens with associated accidental or deliberate release represents a dire risk to the modern world. Compelling evidence to date indicates that the chimeric structure and added furin cleavage site of SARS-CoV-2 was the result of human manipulation in the laboratory. Coronavirus and vaccine patents indicate a foreknowledge of the COVID-19 pandemic, which conveniently serves the interests of the global elites. The new COVID-19 vaccines, hailed as the answer to the pandemic, have potential toxicity, fail to prevent transmission, drive the development of new variants, and over time may predispose recipients to antibody-dependent enhancement (ADE) of infection. Other important technological threats include Internet-based censorship, nano-particulate pollution, electro-pollution and the massive amounts of electromagnetic energy inflicted on humans and Earth’s natural environment. A Technology Bill of Rights is critically needed to protect humanity and salvage what remains of earth’s life support systems.